Assessment of Energy–Environment–Economy Interrelations - Halkos, George (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Energy consumption and economic growth have been of great interest to researchers and policy-makers. Knowing the actual causal relationship between energy and the economy with respect to environmental degradation has important implications for modeling environmental and growth policies. The eleven chapters included herein aim to help researchers, academicians, and especially decision-makers to understand relevant issues and adopt appropriate methods to tackle and solve relevant environmental problems. Various methods from different disciplines are proposed and applied to various environmental and energy issues.